2007
DOI: 10.1021/ic062184+
|View full text |Cite
|
Sign up to set email alerts
|

A Bridge to Coordination Isomer Selection in Lanthanide(III) DOTA-tetraamide Complexes

Abstract: Interest in macrocyclic lanthanide complexes such as DOTA is driven largely through interest in their use as contrast agents for MRI. The lanthanide tetraamide derivatives of DOTA have shown considerable promise as PARACEST agents, taking advantage of the slow water exchange kinetics of this class of complex. We postulated that water exchange in these tetraamide complexes could be slowed even further by introducing a group to sterically encumber the space above the water coordination site, thereby hindering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 46 publications
3
40
1
Order By: Relevance
“…All four chelates have an outer-sphere contribution to relaxivity ( r 1 os ) which contributes about 1.8 mM −1 s −1 to the overall discrete chelate’s relaxivity. (1,2,15) But, for GdTTHA 3− this contribution makes up almost the entire relaxivity of the chelate. (16) In every case this is expected to disappear once the chelate is encapsulated and no longer diffusing close to solvent water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All four chelates have an outer-sphere contribution to relaxivity ( r 1 os ) which contributes about 1.8 mM −1 s −1 to the overall discrete chelate’s relaxivity. (1,2,15) But, for GdTTHA 3− this contribution makes up almost the entire relaxivity of the chelate. (16) In every case this is expected to disappear once the chelate is encapsulated and no longer diffusing close to solvent water.…”
Section: Resultsmentioning
confidence: 99%
“…(1719) Phosphonates are effective groups for generating second sphere relaxivity, carboxylates less so. (17,19) Although almost(15) every chelate has some second sphere relaxivity ( r 1 ss ), it is typically only about 0.8 mM −1 s −1 (20 MHz, 25 °C)(15,17) for the carboxylate-based chelates, but rises to about 2.9 mM −1 s −1 (20 MHz, 25 °C) for GdDOTP 5− . (1,2) GdDOTA − and GdDTPA 2− are “inner-sphere chelates” – relaxivity arises through exchange of water between the inner coordination sphere of Gd 3+ and the bulk solvent.…”
Section: Resultsmentioning
confidence: 99%
“…In order to try to further slow down the coordinated water exchange process through steric hindrance of its dissociation, a new DOTAM derivative ligand was prepared (8O 2 -bridged DOTAM, 38) containing a bridged substituent forming a cycle by joining two trans-amide moieties [431]. However, it was found that the Ln 3+ complexes of this ligand lack an inner-sphere water molecule.…”
Section: Cationic Macrocyclic Lanthanide Complexesmentioning
confidence: 99%
“…A bridged DOTAM chelate(38) [431] was also studied.The crystal structures of several tetramide complexes studied show variability in their Ln 3+ coordination. The [La(21)(H 2 O)(Tf)] 2+ species with the meta-pyridyl substituents has a 10-coordinate structure [425], like for the DOTAM complexes [394], the [Eu(21)(H 2 O)] 3+ (meta-pyridyl) [425], [Eu(26)(H 2 O)] 3+ (glycine ethyl ester) [421] and the [Tb(32)(H 2 O)] 3+ ketone [428] have nine-coordinate SA geometries, and the [Eu(16)(CH 3 OH)] 3+ (p-NO 2 -Ph) [422] and [Eu(15)(H 2 O)] 3+ (phenyl)…”
mentioning
confidence: 99%
“…Published data for LnDOTA (brown) and LnDOTA–(gly) 4 (green) (right graph) are also shown for comparative purposes. 2,11,18 …”
Section: Figurementioning
confidence: 99%